Audit Practice Set Grading Guide. - Modisette, James P. (The Accounting Review, 1973)
The article presents information on a grading guide developed for use in a basic auditing course. The grading guide shown in the article was developed for use in a basic auditing course in which the satisfactory completion of an audit practice case was required. In the initial use of the guide a more objective basis existed for the assigned grade than was available by the use of prior methods. In the following semester, the guide was distributed to the students as a part of the assignment materials for the course. During the semester the quality of the students' work appeared to improve due to a better understanding of the grading process between student and teacher. In addition, the checklist added to the professional aspects of the practice set by placing emphasis on audit documentation and review of working papers. Repeated use of the guide has confirmed the early impressions.